Exposure and injury risk in Swedish elite football: a comparison between seasons 1982 and 2001 - Hägglund, M.; Walden, M.; Ekstrand, J. (Scandinavian Journal of Medicine & Science in Sports, 2003)
The long-term development of injury risk in Swedish male elite football was studied. Two prospective cohort studies from seasons 1982 and 2001 were compared with respect to exposure to football, injury incidence and injury severity. The mean number of training sessions during the season had increased by 68% between 1982 and 2001 (142 vs. 238, P<0.001), whereas teams played more matches in 1982 (49 vs. 41, P=0.02). The total exposure to football had increased by 27%. Three out of four players incurred an injury in both seasons. In 2001, players suffered more training injuries due to an increased training exposure. Accounting for risk exposure, there was no difference in injury incidence or severity between the two seasons. The incidence was 8.3 injuries/1000 h of total exposure (4.6 in training and 20.6 in matches) in 1982, compared to 7.8/1000 h-1 (5.2 in training and 25.9 in matches) in 2001. Major injuries accounted for 9% of all injuries, corresponding to an incidence of 0.8/1000 h of football, in both seasons. A trend from semi-professionalism to full professionalism in Swedish elite football was seen during the last two decades. The injury risk did not change over the same period.